Biblical-Contextual Theology: Narrative Hermeneutics for Contemporary Social Issues - f, sir alex (Hikmat : Jurnal Agama Kristen, 2025)
This study develops and tests a Biblical-Contextual Theologyframework based on narrative hermeneutics to respond tocontemporary social issues in Indonesian urban congregations. Startingfrom the assumption that the Bible is a big story that shapes theimagination of faith and the ethos of praxis, the study formulates a fivestep“Narrative-to-Action” protocol: (1) mapping the text’s storyworld(plot, tension, symbols, resolution), (2) identifying key motifs (e.g.,Exodus, Jubilee, Body of Christ, Incarnation), (3) critical dialogue withlocal social narratives, (4) co-designing ecclesiological responses(liturgy, catechesis, diakonia, digital communication), and (5)implementation-evaluation. The mixed-methods design (dominantlyqualitative) includes textual study, interviews/FGDs, digitalethnography, and a pre-post survey of the Congregation NarrativeTransformation Scale (TNJ) in three pilot congregations. Results showan average pre-post increase of approximately 0.4–0.5 points (scale 1–5) on three TNJ constructs—public theological imagination, ethicaldisposition, and practical participation—strengthened by qualitativethemes: (a) Exodus as a framework for economic liberation (microloanrestructuring), (b) Jubilee as an imagination ofrestoration/redistribution, (c) Body of Christ for digital inclusion &literacy, and (d) Incarnation for hybrid pastoral closeness. The noveltylies in the Narrative Mapping Matrix (NPN) that links story elementsto levers of social change (actors, structures, public imagination,practices, policies) along with its evaluation metrics. The findingsconfirm that narrative hermeneutics combined with a participatoryprocess can operationally bridge the text-context gap and producemeasurable practical changes. Limitations include the moderate samplesize and duration of the intervention; further studies are recommendedto extend the period, expand the locations, and add objective outcomeindicators. This research provides an applicable model for churches,Christian educators, and public servants in designing just, inclusive,and relevant community policies.